The Role of Plant Litter in Driving Plant-Soil Feedbacks - Veen, G. F. (Ciska); Fry, Ellen L.; ten Hooven, Freddy C.; Kardol, Paul; Morriën, Elly; De Long, Jonathan R. (Frontiers in Environmental Science, 2019)
Most studies focusing on plant-soil feedbacks (PSFs) have considered direct interactions between plants, abiotic conditions (e.g., soil nutrients) and rhizosphere communities (e.g., pathogens, mutualists). However, few studies have addressed the role of indirect interactions mediated by plant litter inputs. This has left a major gap in our understanding of PSFs in natural ecosystems, where plant litter is a key component of feedback effects. Here, we propose a framework that integrates rhizosphere- and litter-mediated PSF effects to provide insights into the relative contribution of direct effects mediated by interactions between plants and soil rhizosphere organisms, and indirect effects between plants and decomposer organisms mediated by plant root and shoot litter. We examine three pathways via which litter-mediated PSFs can operate (1) physical effects of litter (layer) traits on seed germination, soil structure, and plant growth; (2) chemical effects of litter on concentrations of soil nutrients and secondary metabolites (e.g., allelopathic chemicals); and (3) biotic effects of saprotrophic soil communities. We assess the role of litter in PSF effects via physical, chemical and biotic pathways to address how litter-mediated feedbacks may play out and we identify critical research gaps that need to be filled in order to understand their relative contribution to PSF effects. We also present one of the first experimental studies to show the occurrence and species-specificity of litter-mediated feedbacks. Formally incorporating the plant-litter feedback pathway into PSF experiments will further our understanding of PSFs under natural conditions.